TRIM71 binds to IMP1 and is capable of positive and negative regulation of target RNAs - Foster, Daniel J. (Cell Cycle, 2020)
TRIM71 is an important RNA-binding protein in development and disease, yet its direct targets have not been investigated globally. Here we describe a number of disease and developmentally-relevant TRIM71 RNA targets such as the MBNL family, LIN28B, MDM2, and TCF7L2. We describe a new role for TRIM71 as capable of positive or negative RNA regulation depending on the RNA target. We found that TRIM71 co-precipitated with IMP1 which could explain its multiple mechanisms of RNA regulation, as IMP1 is typically thought to stabilize RNAs. Deletion of the NHL domain of TRIM71 impacted its ability to bind to RNA and RNAs bound by congenital hydrocephalus-associated point mutations in the RNA-binding NHL domain of TRIM71 clustered closely with RNAs bound by the NHL deletion mutant. Our work expands the possible mechanisms by which TRIM71 may regulate RNAs and elucidates further potential RNA targets.